Comparison of 25G and 27G Quincke Needles’ Effects on Post-Dural Puncture Headache Intensity in Spinal Anaesthesia for Caesarean Section - Andrabi, Syed Raashid; Jain, Anumeha; Lakshimi, Sree (Journal of Neonatal Surgery, 2025)
Background: The size and type of spinal needle used affect post-dural puncture headache (PDPH), which varies from person to person. Thinner Quincke-type spinal needles (25G and 27G) are used to overcome this issue. Thus, this study aimed to assess the incidence and intensity of PDPH following caesarean section (CS). Methods: This study, including a total of 170 primiparous women, was carried out in the Department of Anaesthesia, Centurion University Vishakhapatnam, India from 01/10/2022The women who were scheduled for elective surgical CS under spinal anesthesia were randomly divided into groups 1 and 2, based on the type of Quincke spinal needles used during the procedure (group 1 received 25G and group 2 received 27G). For four days straight after the CS, each patient was evaluated every day, and PDPH frequency and intensity along with other associated factors, were noted. Result: A total of 170 pregnant women of CS were included in this study. Age and weight distribution of pregnant mothers were similar in both groups, with the mean age of 27.1 years in group 1 and 26.5 years in group 2. The mean weight of both groups was 62.0kg and 60.9kg, respectively, for groups 1 & 2. The heart rate (82.8 vs 81.6bpm) and mean BP (91.0 vs 90.1mmhg) between group 1 vs group 2 was similar between the two groups. The incidence of PDPH was higher in group 1 (25G) (16.5%) patients than in group 2 patients (27G) (6.1%) (p<0.05). The severity of headache revealed that the maximum number (10.6%, 09 out of 19 PDPH positive cases) of subjects had a mild type of headache. However, the number of subjects with PDPH, both mild and moderate/severe, was significantly higher in group A cases, who were administered the drug through 25 G Quincke spinal needles for CS delivery. The drug volume in the maximum number of subjects (64.1%, 109 cases out of 170) was introduced with more than 3 ml of anaesthesia drug in both groups. The attempt required to attain CSF is higher in group 2, and a finer needle takes more attempts to collect CSF. Conclusion: In terms of the severity of headache, maximum number of cases presented with mild type headaches, but the number of subjects positive for PDPH was significantly more in subjects who received the drug through 25G Quincke spinal needles for CS delivery.